2021
DOI: 10.1002/onco.13806
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes Predict Progression-Free Survival of Patients with Advanced Breast Cancer Treated with Abemaciclib

Abstract: Background. Abemaciclib is a CDK4/6 inhibitor used to treat hormone receptor-positive, human epidermal growth factor receptor 2-negative (HR+, HER2-) advanced breast cancer (ABC). The prognostic value of patient-reported outcomes (PROs) have been minimally explored for treatment outcomes with CDK4/6 inhibitors. The performance of PROs compared to Eastern Cooperative Oncology Group Performance Status (ECOG-PS) is unknown. Material and Methods. This study pooled data from singlearm trial, MONARCH 1, and randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
(90 reference statements)
2
6
0
Order By: Relevance
“…Previous studies have shown that functional scales (at baseline) are related to survival among cancer patients [19] or advanced cancer patients [20]. Physical functioning might be more predictive of survival than are other functional scales [20]. Second, we demonstrated changes from baseline provide additional information to the baseline QOL score.…”
Section: Discussionsupporting
confidence: 49%
“…Previous studies have shown that functional scales (at baseline) are related to survival among cancer patients [19] or advanced cancer patients [20]. Physical functioning might be more predictive of survival than are other functional scales [20]. Second, we demonstrated changes from baseline provide additional information to the baseline QOL score.…”
Section: Discussionsupporting
confidence: 49%
“…A similar study also reported physical function to be more predictive than ECOG-PS in NSCLC patients treated with atezolizumab monotherapy (26). This growing evidence demonstrates the potential complimentary role of implementing PROs into clinical practice (7,9,(30)(31)(32). However, the integration of PROs into clinical practice poses challenges including time constraints, handling of missing data and literacy differences between patients.…”
Section: Discussionmentioning
confidence: 82%
“…The findings of the present study are consistent with prior findings of patient-reported physical function/physical well-being and ECOG PS providing independent prognostic information. 17 , 20 , 21 It was interesting to note that 12% and 58% of patients classified as ECOG PS 0 reported poor and intermediate physical well-being, respectively. This indicates that 70% of the patients who were defined by their clinicians as ‘fully active, and able to carry on all pre-disease performance without restrictions’ reported limitations in their physical well-being status.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to pool patients with HER2-positive ABC from three different trials that have been treated with contemporary therapies, and the results are consistent with recent findings in other advanced cancers. 16 , 17 , 18 , 19 , 20 , 21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation